Comparison of the efficacy and safety of non-steroidal anti-inflammatory drugs for patients with primary dysmenorrhea: A network meta-analysis. Issue 1 (April 2018) - Feng, Xuan; Wang, Xiaoyun
Objective: Non-steroidal anti-inflammatory drugs are used as first-line treatment of primary dysmenorrhea, but there has been no optimal clinical choice among non-steroidal anti-inflammatory drugs yet. The present study was to assess the relative benefits of different common non-steroidal anti-inflammatory drugs for primary dysmenorrhea patients with a network meta-analysis. Methods: Randomized controlled trials were screened by our criteria and included in the network meta-analysis. Pain relief was considered as primary outcomes and adverse effect was supplied as a safety outcome, while additional rescue, assessment score, and pain intensity difference were secondary outcomes. All the indexes were evaluated with odds ratio or standardized mean difference. Surface under cumulative ranking curve result was used to calculate the ranking of each treatment. Results: Totally, 72 randomized controlled trials of 5723 patients and 13 drugs were included in our study after screening. As for pain relief, all drugs except nimesulide, rofecoxib, and waldecoxib were superior to aspirin (odds ratio with 95% credible intervals, diclofenac: 0.28 (0.08, 0.86), flurbiprofen: 0.10 (0.03, 0.29), ibuprofen: 0.32 (0.14, 0.73), indomethacin: 0.21 (0.07, 0.58), ketoprofen: 0.25 (0.10, 0.64), mefenamic acid: 0.28 (0.09, 0.87), naproxen: 0.31 (0.15, 0.64), piroxicam: 0.15 (0.03, 0.59), and tiaprofenic acid: 0.17 (0.04, 0.63)). Aspirin also required additional rescue when compared with the majority of other drugs (flurbiprofen: 3.46 (1.15, 11.25), ibuprofen: 6.30 (2.08, 20.09), mefenamic acid: 7.32 (1.51, 37.71), naproxen: 2.66 (1.17, 6.55), and tiaprofenic acid: 9.58 (1.43, 94.63)). As for assessment of the whole treatment, ketoprofen, naproxen, rofecoxib, and ibuprofen got higher score significantly than placebo. In addition, ibuprofen performed better than placebo in pain intensity difference. Considering the safety, tiaprofenic acid and mefenamic acid were noticeable in low risk, and indomethacin revealed higher risk than any other drugs. According to the results of network analysis and surface under cumulative ranking curve, flurbiprofen was considered to be the best one among all the treatments in efficacy, and aspirin was worse than most of others. On the other hand, tiaprofenic acid and mefenamic acid were indicated as the safest drugs. Conclusion: Considering the efficacy and safety, we recommended flurbiprofen and tiaprofenic acid as the optimal treatments for primary dysmenorrhea.